2010
DOI: 10.1001/dmp.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

A Toolkit to Assess Medical Reserve Corps Units' Performance

Abstract: ABSTRACTObjectives: The Medical Reserve Corps (MRC) is a national network of community-based units created to promote the local identification, recruitment, training, and activation of volunteers to assist local health departments in public health activities. This study aimed to develop a toolkit for MRC coordinators to assess and monitor volunteer units' performance and identify barriers limiting volunteerism.Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, a few of the tools mentioned in the manuscript are available online (Table 1), including Emergency Preparedness Exercise Evaluation Toolkit, Evaluation Toolkit for the Deployment of MRC Units during Flu Clinics and other Public Health Activities, and Assessment for Disaster Engagement with Partners Toolkit 15 16 , 34 A future research and evaluation program for PHEPR system measurement must be informed by a sound conceptual model of how factors in this complex system interact to influence the course of response and subsequent recovery. Lacking such a model, the field may continue to struggle to find consensus on what is most important to measure and, in turn, may continue to produce metrics that are difficult to apply and validate across different contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few of the tools mentioned in the manuscript are available online (Table 1), including Emergency Preparedness Exercise Evaluation Toolkit, Evaluation Toolkit for the Deployment of MRC Units during Flu Clinics and other Public Health Activities, and Assessment for Disaster Engagement with Partners Toolkit 15 16 , 34 A future research and evaluation program for PHEPR system measurement must be informed by a sound conceptual model of how factors in this complex system interact to influence the course of response and subsequent recovery. Lacking such a model, the field may continue to struggle to find consensus on what is most important to measure and, in turn, may continue to produce metrics that are difficult to apply and validate across different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…To examine response workforce participation and performance, Savoia and colleagues developed and tested 2 questionnaires for Medical Reserve Corps (MRC) volunteers: one to assess performance and attitudes of volunteers, and another to assess barriers that prevented some volunteers from participating in influenza clinics. 34 Factor analysis indicated that 20 items in the Volunteer Self-Assessment Questionnaire could be grouped into 5 factors. Results concerning volunteers' performance were consistent with observations from LHD staff working with the volunteers and external evaluators observing the flu clinics' activities.…”
Section: Criteria and Metrics Related To Workforce Capacity Or Capabimentioning
confidence: 99%
“…The PERRCs addressed the third program objective by conducting critical research to develop evaluation methods, metrics, and modeling approaches that can be used to support capability assessment and reduce system performance variability. Examples of capability assessment strategies developed by the PERRCs included a toolkit to evaluate Medical Reserve Corps performance 34 and studies examining how to better use after-action reports [35][36][37] and exercises [38][39][40][41][42] for performance improvement. PERRC research pursued modeling of various PHP system phenomena, including mass evacuation, 43 the impact of different vaccine distribution strategies, 44,45 infectious disease progression in a population, 46,47 and effects of variation in mitigation strategies, such as the impact of different school closure approaches.…”
Section: Realization Of the Perrc Program Objectivesmentioning
confidence: 99%